Effect of body mass index on survival after spinal cord injury - Fallah, Nader; Noonan, Vanessa K.; Thorogood, Nancy P.; Kwon, Brian K.; Kopp, Marcel A.; Schwab, Jan M. (Frontiers in Neurology, 2024)
Increased mortality after acute and chronic spinal cord injury (SCI) remains a challenge and mandates a better understanding of the factors contributing to survival in these patients. This study investigated whether body mass index (BMI) measured after acute traumatic SCI is associated with a change in mortality. A prospective longitudinal cohort study was conducted with 742 patients who were admitted to the Acute Spine Unit of the Vancouver General Hospital between 2004-2016 with a traumatic SCI. Investigation of the association between BMI on admission and long-term mortality was conducted using Classification and Regression Tree (CART) and Generalized Additive Models (spline curves) from acute care up to 7.7 years after SCI (chronic phase). Multivariable models were adjusted for i) demographic factors (e.g. age, sex, Charlson Comorbidity Index) and ii) injury characteristics (e.g. neurological level, ASIA Impairment Scale, Injury Severity Score). After exclusion of incomplete datasets (n=602), 643 patients were analyzed, of which 102 (18.5%) patients died during a period up to 7.7 years after SCI. CART identified three distinct mortality-risk groups: i) BMI: > 30.5 kg/m2, ii) 17.5 – 30.5 kg/m2 and iii) < 17.5 kg/m2. Mortality was lowest in the high BMI group (BMI > 30.5 kg/m2), followed by the middle weight group (17.5 – 30.5 kg/m2), and was highest in the underweight group (BMI < 17.5 kg/m2) (p-value<0.05). High BMI had a mild protective effect against mortality after SCI (hazard ratio 0.28, 95% CI: 0.09 – 0.88), concordant with a modest “obesity paradox” (p-value<0.05). Moreover, being underweight at admission was a significant risk factor for mortality up to 7.7 years after SCI (hazard ratio 5.5, 95% CI: 2.34 – 13.17). Mortality risk (1 month to 7.7 years after SCI) was associated with differences in BMI at admission. Further research is needed to better understand the underlying mechanisms. Given an established association of BMI with metabolic determinants, these results may suggest unknown neuro-metabolic pathways that are crucial for patient survival.